2021
DOI: 10.3390/ijms22052434
|View full text |Cite
|
Sign up to set email alerts
|

An Extracellular Perspective on CNS Maturation: Perineuronal Nets and the Control of Plasticity

Abstract: During restricted time windows of postnatal life, called critical periods, neural circuits are highly plastic and are shaped by environmental stimuli. In several mammalian brain areas, from the cerebral cortex to the hippocampus and amygdala, the closure of the critical period is dependent on the formation of perineuronal nets. Perineuronal nets are a condensed form of an extracellular matrix, which surrounds the soma and proximal dendrites of subsets of neurons, enwrapping synaptic terminals. Experimentally d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 256 publications
6
77
0
1
Order By: Relevance
“…Two studies have shown circadian/diurnal changes, with higher numbers or intensity of PNNs in the dark phase in rodents (Pantazopoulos et al, 2020 ; Harkness et al, 2021 ). Given that PNNs are altered in many ways throughout central nervous system development, and their maturation is brain region-specific and generally coincides with the end of critical periods of plasticity (for a recent review see Carulli and Verhaagen, 2021 ), it is not surprising that numerous studies have also demonstrated changes in PNNs or their composition during aging (Tanaka and Mizoguchi, 2009 ; Karetko-Sysa et al, 2014 ; Brewton et al, 2016 ; Foscarin et al, 2017 ; Richard et al, 2018 ; Ueno et al, 2019 ; Mafi et al, 2020 ). Overall, changes in PNNs and PV neurons after physiological stimuli appear to be specific to the physiological stimulus, brain region, and the circuits in which PNN-surrounded neurons are embedded.…”
Section: Impact Of Physiological Stimuli On Pnnsmentioning
confidence: 99%
“…Two studies have shown circadian/diurnal changes, with higher numbers or intensity of PNNs in the dark phase in rodents (Pantazopoulos et al, 2020 ; Harkness et al, 2021 ). Given that PNNs are altered in many ways throughout central nervous system development, and their maturation is brain region-specific and generally coincides with the end of critical periods of plasticity (for a recent review see Carulli and Verhaagen, 2021 ), it is not surprising that numerous studies have also demonstrated changes in PNNs or their composition during aging (Tanaka and Mizoguchi, 2009 ; Karetko-Sysa et al, 2014 ; Brewton et al, 2016 ; Foscarin et al, 2017 ; Richard et al, 2018 ; Ueno et al, 2019 ; Mafi et al, 2020 ). Overall, changes in PNNs and PV neurons after physiological stimuli appear to be specific to the physiological stimulus, brain region, and the circuits in which PNN-surrounded neurons are embedded.…”
Section: Impact Of Physiological Stimuli On Pnnsmentioning
confidence: 99%
“…Rampant protease secretion from immune cells propagates their entry through the blood-brain barrier after traumatic injury (Noble et al 2002) or neurodegenerative disorders (Crapser et al 2020) contributing to secondary damage and loss of synapses. However, the fine control of local protease release from growth cones or the leading processes of migrating cells is critically important during developmental pathfinding (Brooks et al 2013) as well as during regeneration or sprouting in the adult (Krystosek and Seeds 1984;Luo et al 2018;Tran et al 2018a;Carulli and Verhaagen 2021;Tran and Silver 2021).…”
Section: The Biology and Transcriptomic Changes Of Microglia After Injurymentioning
confidence: 99%
“…Progenitor cells over-expressing NG2 PG also improve re-myelination through EGFR mediated cell signaling ( Keirstead and Blakemore, 1999 ; Aguirre et al, 2007 ). PNNs surrounding the soma and dendrites of a number of neuronal cell types are prevalent during neural development and maturation ( Carulli and Verhaagen, 2021 ). A similar structure, the perinodal ECM surrounds the axonal nodes of Ranvier and appear after re-myelination, acting as a protective ion-diffusion barrier ( Bekku and Oohashi, 2019 ; Fawcett et al, 2019 ).…”
Section: Mammalian Neuronal Proteoglycansmentioning
confidence: 99%
“…With the identification of the multiple molecular determinants that provide neuronal connectivity, and with new insights into the modulatory extracellular information regulating axon guidance, neural network and synapse formation, a better understanding of the complexity that neurons face in a living organism is beginning to emerge. Attention is now returning to an ancient regulator of cell-cell interaction: the ECM ( Dityatev and Schachner, 2006 ; Dityatev et al, 2010 ; Miyata and Kitagawa, 2017 ; Nicholson and Hrabětová, 2017 ; Ferrer-Ferrer and Dityatev, 2018 ; Quraishe et al, 2018 ; Cope and Gould, 2019 ; Long and Huttner, 2019 ; Chelyshev et al, 2020 ; Jain et al, 2020 ; Wilson et al, 2020 ; Carulli and Verhaagen, 2021 ; Kamimura and Maeda, 2021 ; Shabani et al, 2021 ; Su et al, 2021 ). Among the many matrix components that influence neuronal connectivity, recent studies on the CS-PGs and HS-PGs indicate these ancient molecules form dynamic scaffolds that not only provide a protective environment around cells but are also a source of directive cues that modulate neuronal behavior and synaptic plasticity in tissue development ( Haylock-Jacobs et al, 2011 ; Hayes and Melrose, 2018 ; Hayes et al, 2018 ; Karamanos et al, 2018 ; Hayes and Melrose, 2020a ; Shabani et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%